Senam Yoga dan Aromaterapi terhadap Kualitas Tidur pada Lanjut Usia - Setiawan, Asep Widi Muharom Solih; Nurhalinah, Nurhalinah; Meilianingsih, Lia; Juniarti, Neti; Suharijiman, Suharijiman (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of yoga and aromatherapy on sleep quality in older people. The research method used is a quasi-experiment with a pre-test and post-test group control design. The results showed that the sleep quality in the control group was 2.631, while the sleep quality of the experimental group was 3.723. A p-value of 0.000 (<0.05) was obtained based on statistical tests using the T-Test. In conclusion, there is a significant effect between yoga and aromatherapy on sleep quality in older people. Keywords: Aromatherapy, Sleep Quality, Elderly, Yoga